Autorzy:Karolina Wej, Wojciech Babiański, Ewa Szmytkiewicz, Jerzy Janowicz
Wydawnictwo:Nowa Era
Rok wydania:2015
Rozwiąż równanie. a) x²-18=x(x-2) b) 6x(3-2x)=5+4x(7-3x)4.0 gwiazdek na podstawie 8 opinii

Rozwiąż równanie. a) x²-18=x(x-2) b) 6x(3-2x)=5+4x(7-3x)

3Zadanie
4Zadanie
5Zadanie
6Zadanie
7Zadanie
8Zadanie
9Zadanie

`a) \ \ x^2-18=x(x-2)`

`x^2-18=x^2-2x \ \ \ \ \ \ |-x^2`

`-18=-2x \ \ \ \ \ |:(-2)`

`9=x`

`x=9`

`b) \ \ 6x(3-2x)=5+4x(7-3x)`

`6x*3-6x*2x=5+4x*7-4x*3x`

`18x-12x^2=5+28x-12x^2 \ \ \ \ |+12x^2`

`18x=5+28x \ \ \ \ \ \ \ |-28x`

`-10x=5 \ \ \ \ \ \ \ |:(-10)`

`x=-5/10=-1/2`